Catalytic conversion of carbon dioxide into dimethyl carbonate using reduced copper-cerium oxide catalysts as low as 353 K and 1.3 MPa and the reaction mechanism - Wada, Seiki; Oka, Kazuki; Watanabe, Kentaro; Izumi, Yasuo (Frontiers in Chemistry, 2013)
Synthesis of dimethyl carbonate (DMC) from CO2 and methanol under milder reaction conditions was performed using reduced cerium oxide catalysts and reduced copper-promoted Ce oxide catalysts. Although the conversion of methanol was low (0.005–0.11%) for 2 h of reaction, DMC was synthesized as low as 353 K and at total pressure of as low as 1.3 MPa using reduced Cu–CeO2 catalyst (0.5 wt% of Cu). The apparent activation energy was 120 kJ mol–1 and the DMC synthesis rates were proportional to the partial pressure of CO2. An optimum amount of Cu addition to CeO2 was 0.1 wt% for DMC synthesis under the conditions at 393 K and total pressure of 1.3 MPa for 2 h (conversion of methanol: 0.15%) due to the compromise of two effects of Cu: the activation of H2 during reduction prior to the kinetic tests and the block (cover) of the surface active site. The reduction effects in H2 were monitored through the reduction of Ce4+ sites to Ce3+ based on the shoulder peak intensity at 5727 eV in the Ce L3-edge X-ray absorption near-edge structure (XANES). The Ce3+ content was 10% for reduced CeO2 catalyst whereas it increased to 15% for reduced Cu–CeO2 catalyst (0.5wt% of Cu). Moreover, the content of reduced Ce3+ sites (10%) associated with the surface O vacancy (defect sites) decreased to 5% under CO2 at 290 K for reduced Cu–CeO2 catalyst (0.1wt% of Cu). The adsorption step of CO2 on the defect sites might be the key step in DMC synthesis and thus the DMC synthesis rate dependence on the partial pressure of CO2 was proportional. Subsequent H atom subtraction steps from methanol at the neighboring surface Lewis base sites should combine two methoxy species to the adsorbed CO2 to form DMC, water, and restore the surface O vacancy.